The immersion method for improving basic english vocabulary knowledge to tenth-grade students at unidad educativa UPSE. La Libertad, province of Santa Elena, school year 2021-2022 - Reyes Limones, Marvelle Elizabeth (2021)
The present research project attempts to improve the English vocabulary knowledge of the forty-nine Tenth-Graders at Unidad Educativa "UPSE" by creating and proposing a Didactic Guide focused on what the Immersion Method establishes. In the educational setting, immersion aims at using the target language as the medium of instruction of academic, cultural, and subject content that supports language learners to be highly involved in the lessons. For the accomplishment of the main purpose, the quantitative and qualitative methods were used, which allowed the researcher to apply several techniques to gather relevant data, such as observation, interview, and survey. The analyzed information helped to have a better understanding of the students' needs in learning meaningful vocabulary. This paper suggests a set of immersive content vocabulary activities based on the school's curriculum and topics of interest. Furthermore, those were designed to endow the educator with a tool that seeks to decrease the gaps in the teaching-learning process and encourage learners to put new words into practice while developing their English skills.